2005
DOI: 10.1081/ias-200051996
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Chemiluminescent Immunoassay for NF‐κB–DNA Binding Activity

Abstract: Nuclear factor-kappaB (NF-kappaB) is a ubiquitous redox-sensitive transcription factor involved in the pro-inflammatory response to several factors, including cytokines and oxidative stress. Upon activation, NF-kappaB translocates into the nucleus and binds to specific nucleotide sequences. The cellular responses to inflammatory and stress signals have been implicated in disease conditions, such as atherosclerosis, cancer, diabetes, and Alzheimer's disease. The conventional method for detection of NF-kappaB -D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…To date, a variety of methods have been explored for DNAbinding transcription factor detection. These involve the electrophoretic mobility shift assay (EMSA), 7 DNA footprinting, 8 enzyme-linked immunosorbent assay (ELISA) 9 and electrochemical techniques. 10 However, the aforementioned methods are generally tedious, laborious and expensive, which hinder them from more extensive applications.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of methods have been explored for DNAbinding transcription factor detection. These involve the electrophoretic mobility shift assay (EMSA), 7 DNA footprinting, 8 enzyme-linked immunosorbent assay (ELISA) 9 and electrochemical techniques. 10 However, the aforementioned methods are generally tedious, laborious and expensive, which hinder them from more extensive applications.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional methods for transcription factor detection are electrophoretic mobility shift assay (EMSA) [11], DNA footprinting assay [12], Western blotting assay [13] and enzyme-linked immunosorbent assay (ELISA) [14]. These methods require radioisotope labels and/or specific antibodies against each target protein, which limits their extensive applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to establish a new excellent method. In recent years, chemiluminescent immunoassay (CLIA) has been widely applied to the detection of drug concentration (Feng et al, 2005;Gupta et al, 2005;Shukla and Krag, 2005;Zamora et al, 1999). A study showed that CLIA detected chloramphenicol successfully (Lin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%